The Genetic Variation of Ace Gene Rs4343 Has Lack Association With Pre-Eclampsia: Case-Control Study In Jambi Malay Population - Puspasari, Anggelia; Herlambang, Herlambang; Maharani, Citra; Perkasa, Tengku Arief Buana; Enis, Rina Nofri; Tarawifa, Susan; Syukur, Astian Nathaniel (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: The PE is leading cause of maternal and neonatal mortality and morbidity worldwide. The etiology of PE remains not yet clearly identified, genetics contributed 20-40% of PE. The variation of the rs4343 gene was significant as a risk factor for PE and the severity of PE with effect sizes varying between studies. To the best of our knowledge, the association of rs4343 in the ACE gene for PE risk has not been reported to the population of Indonesia, especially the Jambi Malays. Aims: This study aims to reveal the association of Genetic Variation of ACE gene rs4343 with preeclampsia. Methods: This recent study was case-control, 78 pregnant women matching based on age and pregnancy number participated in this study. The preeclampsia diagnosis is based on the criteria of the American College of Obstetricians and Gynecologists. The genotyping method was tetra ARMS-PCR. Bivariate statistical analysis was performed. Results: The proportion of the AA genotype and AG genotype was slightly different between the two groups, but all GG genotypes suffered preeclampsia. The recessive model reported the GG/AG genotype has a higher risk of PE than the AA genotype (p-value 0.784; OR 1.16, 95% CI (0.40-3.41)). The allele model reported that the G allele (p-value 0.338; OR 1.59, 95% CI (0.62-4.14)) had a higher risk than the A allele. However, all those differences do not reach statistically significant. Conclusion: Genetic Variation of ACE gene rs4343 Has Lack Association with Pre-eclampsia.